Using Technology for Learning in Early Childhood Education : A Review of Asian Countries - Reza Edwin Sulistyaningtyas; Febru Puji Astuti; Prasetyo Yuliantoro (Journal of Education and Teaching Learning, 2023)
Technology is one of the applicable tools in early childhood education learning, and its use necessitates the teachers to play important roles in the classroom. Hence, this research discusses a systematic review of technology use for learning during early childhood education in Asian countries. Empirical studies published between 2015-2022 and identified through systematic screening were examined to eventually obtain 16 articles with subjects spread across China, Jordan, Taiwan, Turkey, Hong Kong, Malaysia, Kuwait, Indonesia and South Korea. The result of this study show that implemented technology in the class can had a positive effects on teacher and children of self-confidence, curiosity, creativity, motivation, interest in learning, children’s emotional (helping them control emotions and overcome fear, shame, and anxiety), social (increasing their communication and interaction with others), moral (assisting in the development of ethics), and physical/health abilities. Benefits of technology in the classroom, as well as self-efficacy, were the supporting factors, while the inhibitors were their lack of understanding in integrating technology into pedagogy, limited school budgets, and the negative impact on children’s health.